Assessing the Effectiveness of Ukrainian Customs Service Personnel: A Perspective on KPI Implementation - Oleksandr Cherkunov (Lex Portus)
The article discusses how the State Customs Service of Ukraine (SCSU) implements procedures for assessing its effectiveness using key performance indicators (KPIs). It outlines the regulatory framework governing this process and describes the anticipated outcomes for both internal and external functions of the customs authorities. The paper reviews the links between the proposed KPI-based assessment system, national strategic planning documents, global and regional standards, and the WCO Performance Measurement Mechanism. The effectiveness indicators used by various non-state actors and the expert community for assessing the SCSU are compared with the relevant indicators proposed in the 2024 draft laws. Additional KPIs are suggested for evaluating the quality and effectiveness of customs personnel and the implementation of program documents.